Studi Perbandingan Fitur-Fitur Aplikasi Al-Quran Digital Karya Greentech Apps Foundation dan Aplikasi Al-Quran Muslim Media untuk Mengetahui Perbedaan Kedua Fitur aplikasi - Yani, Ahmad; Putra, Hepni; Andika, Andika; Nisa, Muria Khusnun; Yunus, Eka Mulyo (Jurnal Riset Agama, 2021)
Digitalization of the Koran is a process of changing the vehicle from the beginning of the Koran being limited to written printed form to digital, for example, the Koran (tafsir and pe — word) by Greentech Apps Foundation and al-Quran interpretation and word by word by Muslim Media. Not many people know information about the background of the formation and differences related to the features of the two applications. The purpose of this research is to find out the background of the formation, features, advantages, and disadvantages, and to compare the features of the two applications. The method used in this article is descriptive-analytical. The software that will be investigated in this research is the application of the Koran (tafsir and pe— word) by Greentech Apps Foundation and Al-Quran Muslim Media. Researchers assume that each application must have a significant comparison. This assumption is proven by examining the features of the two applications. This study concludes that the two applications can be compared in terms of features of interpretation, translation per word, audio, recitation, background display, dictionaries, prayers, and prayer schedules. Through this research, the researcher recommends programming experts and application developers so that in the future they can develop digital Al-Quran applications by prioritizing the advantages of comparing the two applications or even adding even better features to become a superior application in the future.